Photosynthesis as a temperature indicator in Quercus ilex L. (Global and Planetary Change, 2000)
Net photosynthesis Pn , stomatal conductance gs , leaf temperature LT , transpiration rate . . . . E and in vivo chlorophyll fluorescence were monitored February 1996–February 1997 in Quercus ilex plants growing in the climax area Rome and . in the Garda lake region. Photosynthetic activity is an appropriate temperature-dependent functional trait linked to plant metabolism and performance. We employed photosynthesis as a stress temperature indicator. Regression analysis showed that in such regional climatic conditions, net photosynthetic rates were primarily correlated with temperature. The introduction of rainfall in the function did not significantly improve the theoretical prevision, in the range of temperature and rainfall analysed. The favourable leaf temperatures allowing 90–100% of the highest photosynthetic rates were 14–288C, decreasing over 50% when leaf temperature were respectively below 68C and over 378C: the low potential photochemical efficiency of 0.71 PSII Fv . rFm at Castelporziano during summer, confirmed the state of stress. Transpiration rates remained high with the increase of leaf temperature in summer, in spite of the 46% decrease of stomatal conductance. Nevertheless, this decrease allowed the maintenance of acceptable Pn rates in stressful conditions. The potential productivity of Q. ilex lied on high peaks of activity during periods of lower evaporative demand and a rapid stomatal response to an increase in air temperature and soil water deficit. Although it is difficult to forecast Q. ilex productivity and plant structure, we may hypothesize its future presence in the Mediterranean Basin by the capability of vegetative activity in a wide range of temperatures, the high stomatal control in stressful conditions, the high plasticity index and water use efficiency WUE .

Relationship between photosynthetic activity and chlorophyll content in an isolated Quercus ilex L. tree during the year (Photosynthetica, 1998)
The relationship between chlorophyll (Chl) content and net photosynthetic rate (PN) in an isolated Quercus ilex tree, growing inside Villa Pamphili Park in Rome, was explored. The highest Pn was in March, May and September (10.1 umol.m-2.s-1, maximum rate). Pn decreased by 65% (with respect to the yearly maximum) when leaf temperature reached 34ºC, and by 50% when leaf temperature was 9ºC. The highest Chl contents were in April, October [1.47g.kg-1 (d.m.), maximum value], and December. The lowest Chl content was found in July (0.78 g.kg-1). The decrease of PN in July was in close connection with the decrease of Chl content. On the contrary, the high Chl content during winter did not correspond with PN of this season. Discordances between Chl content and PN over the year influenced the regression analysis, which although positive did not show very high correlation coefficients (r=0.79. The high Chl (a+b) content during most of the year indicated that the photosynthetic apparatus remained basically intact also during stress periods.

Edaphic characteristics of Quercus suber woods in Latium (Rendiconti Lincei, 1997)
{In this paper the results are reported of a soil survey done in selected sites of Latium un- der the most significant Quercus suber woods (Cytiso-Quercetum suberis Testi, Pignatti and Lucattini 1994) previously studied from a phytosociologicat point of view. After describing the dominant soil type of each area, physical-chemical characteristics have been analysed in order to point out the significance of edaphic factors in the distribution and floristic composition, of the Quereus suber co,noses. Bioclimatic, structural and edaphic features of this vegetation showed a great convergence; among all the parameters examined, AWC resulted to be the most effective one in conditioning the mesophilous character of Quercus suber coenoses growing in Latium. In this respect this type of vegetation shows rather strong affinities with mixed Quercztr cerrz} woods, both in the floristic composition and in the edaphic requirements, as already suggest- ed in the most recent phytosociological studies.